2015
DOI: 10.1016/j.jcps.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Lasting performance: Round numbers activate associations of stability and increase perceived length of product benefits

Abstract: Consumers prefer products that deliver benefits for a longer time. For instance, caffeinated drinks are consumed for energy, but the key characteristic that performs this benefit—caffeine—tends to wear off in its effects. How can marketers communicate the lasting performance of product characteristics? This work proposes that numbers used in conveying product characteristics—round (200 mg) or precise (203 mg)—influence consumers' perception of lasting performance and product attitudes. More specifically, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Respondents were randomly assigned to one of the conditions (hedonic vs. utilitarian) and asked to imagine purchasing a music festival ticket (vs. home music equipment) that included four virtual workshops (vs. four hardware pieces) for $250. We measured their perceived psychological ownership on a three‐item scale adapted from Pena‐Marin and Bhargave (; “I feel a very high degree of personal ownership of it”, “I feel like I own it”, “I feel like it is mine”; 1 = strongly disagree; 7 = strongly agree; α = .95; M hedonic = 3.7, M utilitarian = 4.5; F [1, 101] = 2.9, p = .02). We also included a manipulation check to measure whether they perceived the item as hedonic or utilitarian (1 = very utilitarian; 7 = very hedonic; M hedonic = 5.3 M utilitarian = 2.5; F [1, 101] = 1.7, p = .000).…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were randomly assigned to one of the conditions (hedonic vs. utilitarian) and asked to imagine purchasing a music festival ticket (vs. home music equipment) that included four virtual workshops (vs. four hardware pieces) for $250. We measured their perceived psychological ownership on a three‐item scale adapted from Pena‐Marin and Bhargave (; “I feel a very high degree of personal ownership of it”, “I feel like I own it”, “I feel like it is mine”; 1 = strongly disagree; 7 = strongly agree; α = .95; M hedonic = 3.7, M utilitarian = 4.5; F [1, 101] = 2.9, p = .02). We also included a manipulation check to measure whether they perceived the item as hedonic or utilitarian (1 = very utilitarian; 7 = very hedonic; M hedonic = 5.3 M utilitarian = 2.5; F [1, 101] = 1.7, p = .000).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, 400 calories would be a more imprecise estimate than 417 calories because of the presence of two ending zeros. A growing body of work has shown that imprecision level influences source judgments in a number of contexts (Isaac, Brough, & Grayson, ; Jerez‐Fernandez et al, ; Pena‐Marin & Bhargave, ; Schindler & Yalch, ; Wadhwa & Zhang, ; Xie & Kronrod, ; Yan & Duclos, ; Zhang & Schwarz, ) including estimates (Hayward & Fitza, ; Jerez‐Fernandez et al, ; Mason et al, ; Yaniv & Foster, ). Building upon the above and other related work, we suggest that if an estimate is revealed to be inaccurate, then imprecise (vs. precise) estimates generate higher (lower) source trustworthiness because they (dis)confirm consumers’ initial accuracy expectations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Finally, research on round numbers (Pena-Marin & Bhargave, 2015;Wadha & Zhang, 2015) suggests that a roundup request may reduce consumers' perceived pain of donating by creating mild positive affect. Although both a roundup and flat request may involve a round number (i.e., the total and donation, respectively), which consumers tend to like (Pena-Marin & Bhargave, 2015;Wadha & Zhang, 2015), only the roundup request explicitly invokes roundedness (i.e., would you like to round up your total to the next whole dollar and donate the difference?) and invariably results in a round number for the overall total.…”
mentioning
confidence: 99%